Transitions in secondary education in Sub-Saharan Africa : equity and efficiency issues. (World Bank working paper, 2008)
"Transitions in Secondary Education in Sub-Saharan Africa is part of the World Bank Working Paper series. These papers are published to communicate the results of the Bank's ongoing research and to stimulate public discussion." "This working paper discusses equity and efficiency issues in secondary education transitions in Sub-Saharan Africa. Its main purpose is to identify and analyze national, regional, and local measures that may lead to the development of more efficient and seamless transitions between post-primary education pathways"--Page 4 of cover